Effect of post-irradiation deformation on the tl of Cu++ doped nacl crystals - Dubey, K K; Nayar, V (Recent Research in Science and Technology, 2012)
The effect of post, irradiation deformation on the TL of γ-irradiated undoped and Cu++ doped NaCl crystals for different impurity concentrations and radiation doses have been studied. In the case of post-irradiation deformation, the two TL peak are found for γ-irradiated undoped and Cu++ doped NaCl crystals at 393ï‚°K and 464ï‚°K respectively. The intensity of both the peak decreases with increasing post-irradiation deformation of the crystals, however, the peak temperatures Tm1 and Tm2 do not change in the post-irradiations deformation of the crystals. There is no occurrence of post-irradiation deformation generated new TL peak in Cu++ doped NaCl crystals. The deformation bleaching as well as enhanced number of the compatible electron traps are responsible for the effect of post-irradiation deformation on the TL of crystals.